Spoznavanje nekaterih pojmov (procesov) preko naravoslovnih poskusov v vrtcu - Petek, Darija (Revija za elementarno izobraževanje, 2010)
Learning about certain notions (processes) via natural science experiments in kindergarten. The basic objective in this research was to set a natural science experiment as a basic which will help a child confirm and upgrade his or her own idea or to change and understand it. Before and during the experiments, children were looking for possible answers to the posed question reflected on them and focused on finding a solution to the problem. This has helped us attain their initial ideas which were then either confirmed during the experiment or changed by children based on the conclusions drawn from the experiment. Their own participation allowed them to change and understand a naive explanation.